2013
DOI: 10.1128/jvi.02380-13
|View full text |Cite|
|
Sign up to set email alerts
|

Epstein-Barr Virus and Human Herpesvirus 6 Detection in a Non-Hodgkin's Diffuse Large B-Cell Lymphoma Cohort by Using RNA Sequencing

Abstract: Herpesviridae is a large family of DNA viruses that can infect and cause disease in humans. Epstein-Barr Virus (EBV) and human herpesvirus 6 (HHV-6) are two members of this family that are highly ubiquitous and have been associated with mononucleosis and exanthema subitum (roseola), respectively. In addition, EBV is a wellknown oncovirus that is associated with several malignancies, including nasopharyngeal carcinoma, gastric carcinoma, and lymphomas. HHV-6 is an emerging pathogen that has not been defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 25 publications
(24 reference statements)
4
51
1
Order By: Relevance
“…Remarkably, BZLF1 lytic gene expression is suggestive of an abortive lytic cycle linked to tumor progression, as proposed by Strong et al, who recently reported high immediate early lytic expression in DLBCL cases without other lytic genes. 33 A strong correlation among all EBNAs quantified was observed, which is predictable, as in latency III, these EBNA mRNAs are generated by alternative splicing of long primary transcripts initiated either from the tandemly repeated Wp promoter or the upstream Cp promoter. 34 Alternatively, in B cells displaying latency III type infection, LMP1 and LMP2A/B expressions are dependent on expression of EBNA2.…”
Section: Discussionmentioning
confidence: 91%
“…Remarkably, BZLF1 lytic gene expression is suggestive of an abortive lytic cycle linked to tumor progression, as proposed by Strong et al, who recently reported high immediate early lytic expression in DLBCL cases without other lytic genes. 33 A strong correlation among all EBNAs quantified was observed, which is predictable, as in latency III, these EBNA mRNAs are generated by alternative splicing of long primary transcripts initiated either from the tandemly repeated Wp promoter or the upstream Cp promoter. 34 Alternatively, in B cells displaying latency III type infection, LMP1 and LMP2A/B expressions are dependent on expression of EBNA2.…”
Section: Discussionmentioning
confidence: 91%
“…The average number of reads per cell line was approximately 164 million, ranging from 74.6 million to 209.8 million. Based on our previous investigations of microbial agents in biological specimens and cell lines (13)(14)(15), these read depths were deemed to be well above the minimum levels required to detect meaningful pathological infections.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer genome characterization initiatives, including The Cancer Genome Atlas (TCGA), have provided next-generation sequencing (NGS) data on thousands of tumors and various human cancers, and these data are valuable sources for understanding the transcriptional basis of tumorigenesis, as well as variations in tumors (4). Computational techniques have been used to quantify viral presence in many cancers, thereby accelerating the identification of virus-disease associations (5)(6)(7). However, the increasing sensitivity of these techniques may also reveal previously unappreciated viral contaminations that could be erroneously associated with the disease (8)(9)(10).…”
mentioning
confidence: 99%